Effects of sludge enhanced aeration on nutrient contents and phytotoxicity of anaerobically digested centrate. (July 2018) - Luo, Wenhai; Zhang, Bangxi; Bi, Yanmeng; Li, Guoxue; Sun, Qiaoping
Abstract: In this study, we investigated the impact of intensive aeration pre-treatment on nutrient contents and phytotoxicity of anaerobically digested manure centrate. Activated sludge from conventional wastewater treatment plants was added to reinforce the aeration process. Results show that the addition of activated sludge did not negatively affect the nutrient contents, but significantly reduced the phytotoxicity of digested centrate, as indicated by an enhancement of seed germination index, during the aeration treatment. Based on the orthogonal experiment and following statistical analysis, the lowest phytotoxicity of digested centrate could be achieved under the aeration conditions: sludge concentration of 6 g/L, aeration time of 2 h, gas/water ratio of 40:1, and pH = 6.5. Of these operational parameters, the digested centrate pH dominantly determined its nutrient contents (e.g., amino acids, total phosphorus, and ammonium) and phytotoxicity. These results were further verified by hydroponic experiments, which showed that using digested centrate after sludge enhanced aeration as the nutrient solution facilitated the growth and dry biomass of maize. Highlights: Activated sludge improved the aeration pre-treatment of digested manure centrate. Phytotoxicity of digested centrate was notably reduced by sludge enhanced aeration. Sludge enhanced aeration was optimized based on the orthogonal experiment. PH dominantly governed nutrient contents and phytotoxicity of digested centrate. Maize growth was enhanced when hydroponically nurtured by aerated digested centrate.